2020
DOI: 10.1002/jper.20-0566
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a change in classification criteria on the prevalence of peri‐implantitis: A cross‐sectional analysis

Abstract: Background Peri‐implantitis is a frequent finding but estimates of its prevalence vary widely. This may be due to the wide variety of disease definitions. In 2017 the World Workshop on Periodontal and Peri‐implant Diseases and Conditions established new criteria for disease definitions. The aim of this study is to assess the potential impact of a new definition on the future reporting of peri‐implant disease. Methods Data from a 2015 report of peri‐implant prevalence were examined using the new diagnostic crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…e same effect was seen in the study of Pimentel et al [32] for the impact of PPD ≥6 mm on peri-implantitis. In the study of Dalago et al [21], a history of periodontitis appeared to be a risk indicator of peri-implantitis only after multivariable analysis was conducted with an OR � 2.2. ese different observed associations may reflect the variability of clinical parameter interactions in the studied populations, as well as the use of different peri-implant disease definitions [47]. In the present study, peri-implant soft-tissue diseased sites defined as PiPD > 4 mm + BOPi remained independently associated to some demographic, periodontal, implant, and prosthesis parameters, suggesting that these parameters could influence periimplantitis triggering, as shown previously for other periodontal parameters in a similar cohort [28].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…e same effect was seen in the study of Pimentel et al [32] for the impact of PPD ≥6 mm on peri-implantitis. In the study of Dalago et al [21], a history of periodontitis appeared to be a risk indicator of peri-implantitis only after multivariable analysis was conducted with an OR � 2.2. ese different observed associations may reflect the variability of clinical parameter interactions in the studied populations, as well as the use of different peri-implant disease definitions [47]. In the present study, peri-implant soft-tissue diseased sites defined as PiPD > 4 mm + BOPi remained independently associated to some demographic, periodontal, implant, and prosthesis parameters, suggesting that these parameters could influence periimplantitis triggering, as shown previously for other periodontal parameters in a similar cohort [28].…”
Section: Discussionsupporting
confidence: 72%
“…e number of implants was correlated with tooth loss, which could reflect the impact of periodontal risk indicators [24], as suggested for implant failure [46]. Using multivariable analysis, the impact of implant number on the peri-implant tissue parameters was reduced, as shown for peri-implantitis [31,47]. However, it was still present for Bli, suggesting that other risk factors specifically correlated with the implant number may influence peri-implant soft tissue conditions [23].…”
Section: Discussionmentioning
confidence: 83%
“…A recent change in the classification of peri-implantitis has lead to an increased difficulty in the interpretation of the prevalence of this disease [2]. Nowadays, we can assume for peri-implantitis the presence of bleeding or suppuration with gentle pressure on probing and some variations from previous examinations, such as increased probing depth and increased bone loss; in the case of the absence of previous examinations, periimplantitis is defined as presence of bleeding and/or suppuration on gentle probing, probing depths ≥6 mm, and bone levels ≥3 mm apical to the most coronal portion of the intraosseous part of the implant, as stated by the American Academy of Periodontology and the European Federation of Periodontology [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is very important to consider that different classifications, with restrictive diagnostic criteria, are associated with significantly reduced presence of peri-implantitis [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, several authors have indicated that frequent patients recalls are involved in peri-implantitis prevention, and a close recall scheme is essential [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%